Psico-oncologia na mastologia: análise das teses e dissertações publicadas na rede mundial de computadores (Internet) no período 2005‐2009 - Morais, Barbara Luisa Silva de Almeida (2010)
This study is a review of the scientific production of the Brazilian Post‐graduation work in Psycho‐Oncology in Mastology, from theses and dissertations published between 2005 to 2009, whose goal is to give an overview of scientific literature in this area, in order to verify the state of the art in this new discipline. Another objective was to confront the experience as having a diagnosis of breast cancer with the literature review. Eleven studies were found and obtained from the surveys, the scientific production was described in an approximate sequence of the historical events prior to the onset of disease, impact of early emotional ties, the stress response and behavior of women with breast cancer; communicating bad news from the perspective of the patient as well as their families; of meaning and meaning production and reception of health promotion, sense of self‐care and be careful; ways of coping, quality of life, aspects of personality and cancer recurrence, and the daily institutional care leavers; issues addressed by the group of patients in the waiting room, as well as from my own experience as a woman with breast cancer, a mother and a researcher.